The rural mother's experience of caring for a child with a chronic health condition: An integrative review. Issue 13 (1st June 2018) - Bristow, Sally; Jackson, Debra; Shields, Linda; Usher, Kim
Abstract : Aims and objectives: To identify and review the literature on rural mothers' experiences in caring for a child with a chronic health condition. Background: Families living with a child who has a chronic health condition experience many challenges; these are often amplified for families living in rural areas, where issues such as the distance from services add further challenges the family must manage. Like many children, rural children with chronic health conditions are primarily cared for by their mothers. The additional strain of geography creates its own unique experiences for mothers who need to access the high‐quality care that their child requires. Design: Integrative literature review using the Equator PRISMA guidelines. Methods: A search of databases; Cochrane, CINAHL, Ovid, PubMed, ProQuest Health and Medicine, Informit and Scopus for studies published between 2005–2016 using an integrative review approach. A total of 1, 484 studies were identified with an additional six studies found through snowballing. The search resulted in seven studies being meeting the inclusion criteria after using the Critical Appraisal Skills Programme. Results: Data from the seven articles were analysed, and t he mothers' experiences were synthesised into five themes: "struggling for resources, " "barriers in accessing services, " "strain of decision‐making, " "mother's physical and emotional breakdown" and "the daily management of family activities". These five themes formed the basis of this article. Conclusions: The findings indicate that mothers from rural areas face additional barriers related to their rurality, including transportation difficulties, socioeconomic status and social isolation, and are challenged by limited access to specialty medical services, educators and allied health professionals. The literature review outcome will assist in informing nursing practice through identifying and allocating resources to reduce these barriers; rural mother experience will assist in enabling the child to reach their full developmental potential. Relevance to clinical practice: There is a need for health professionals to understand the challenges and barriers rural mothers face in accessing services. Nurses can assist rural mothers to navigate and access the appropriate services in order to reduce health inequity, increase accessibility to services and reduce rural disadvantage for their child. Nurses and health professionals are in an ideal position to develop future models of care that optimise health outcomes and enable equity and access to services for rural children with chronic conditions similar to those experienced by their urban counterparts.